Effect of grain size on the electrical failure of copper contacts in fretting motion. (July 2017) - Noh, H.J.; Kim, J.W.; Lee, S.M.; Jang, H.
Abstract: The influence of grain size on degradation of electrical contacts during fretting wear was investigated. Copper polycrystals with grain sizes of 2–162 µm were used to examine friction, wear, and electrical contact resistance. The results showed that the electrical contact failure was caused by the compact oxide layer produced at the contact junction. Copper specimens with smaller grains had a longer lifecycle because of grain-size strengthening. However, this strengthening effect was limited to a critical grain size and, with further increase in grain size, plastic deformation underneath the contact surface played a major role in delaying the contact failure caused by oxide formation on the fretting surface. Highlights: Compact oxides produced by fretting wear caused electrical contact failure. Attrition or deformation of the surface determined lifecycle of electrical contacts. The failure mode was dependent on the grain size of the contact material. Polycrystals with small grains showed a longer lifecycle by grain-size effects. Polycrystals with grains bigger than 60 μm also delayed electrical contact failure.